If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -13 = -2x + -7 Reorder the terms: -13 + 4x = -2x + -7 Reorder the terms: -13 + 4x = -7 + -2x Solving -13 + 4x = -7 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -13 + 4x + 2x = -7 + -2x + 2x Combine like terms: 4x + 2x = 6x -13 + 6x = -7 + -2x + 2x Combine like terms: -2x + 2x = 0 -13 + 6x = -7 + 0 -13 + 6x = -7 Add '13' to each side of the equation. -13 + 13 + 6x = -7 + 13 Combine like terms: -13 + 13 = 0 0 + 6x = -7 + 13 6x = -7 + 13 Combine like terms: -7 + 13 = 6 6x = 6 Divide each side by '6'. x = 1 Simplifying x = 1
| -20=8x-5(x+1) | | t+a=b | | (4z-u)(6z+5u)= | | 2/5y | | 60=10x-10 | | 5x-3=447 | | 42y=12-5+49 | | 1/2(4x-2)-3x=-6 | | 3/7X4/5 | | 10=3n+5-4(n-2) | | 3=-4x-9+x | | 3w+8(2w-6)=2+14w | | 36-4x=2x+6 | | (5x-4)(x^2-3x+1)= | | -8(x-3)-10=-2 | | y=-2x+29 | | 3m^3-12m^2=15m | | 5/15x5/15 | | 4x-5x+3=7 | | 98-3x=4x+4 | | 3x-4+2x+8+4x+10=36 | | w-6=a | | 3(w-1)+3(w-2)=3 | | 6d-8=-2 | | (4x+5)(2x^2+7x+8)= | | n-12=-17 | | 2x-3/4x+9 | | 10*36/10=-36 | | 6x+y+4=-15+9y-x | | f(18)=4x-2 | | 2m=5/3m-1 | | -3(4x-2)=6 |